Research on Ripple Suppression of Switching Power Supply Based on Computer Simulation Software Multisim - Liu, Songmei (International Journal of Informatics and Information Systems, 2023)
With the development of computer software technology, it is widely used in switching power supply ripple suppression. This article mainly analyzes the causes of ripple, ripple suppression methods and circuit design in the Multisim environment. It also studies simulation analysis methods.